Experimental models of early exposure to alcohol: a way to unravel the neurobiology of mental retardation - Alberto Granato (Frontiers Research Topics, 2015)
Excessive alcohol drinking represents a major social and public health problem for several countries. Alcohol abuse during pregnancy leads to a complex syndrome referred to as fetal alcohol spectrum disorders (FASD), chiefly characterized by mental retardation. The effects of early exposure to ethanol can be reproduced in laboratory animals and this helped to answer several key questions concerning the human pathology. The interest of experimental models of FASD is twofold. First, they increase our knowledge about the dose and modality of alcohol consumption able to induce damaging effects on the developing brain. Second, experimental models of FASD can provide useful hints to elucidate the basic mechanisms leading to the intellectual disability. In fact, experimental exposure to alcohol can be carried out during discrete, often very restricted, time windows. As a consequence, FASD models, though depending on the multifaceted interference of alcohol with several molecular pathways, can provide valuable information about which specific developmental periods and brain areas are critically involved in the genesis of mental retardation. Putting together data obtained through several experimental paradigms of alcohol exposure and those deriving from other genetic and non-genetic models, one can figure out to what extent different types of mental retardation share common pathogenetic mechanisms. The present Research Topic is aimed at establishing the state of the art of the current research on experimental FASD, focusing on differences and homologies with other types of intellectual disability. The ultimate goal is to find out a common roadmap in view of future therapeutical approaches.